PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TIME TOKEN UNTUK MENINGKATKAN AKTIVITAS HASIL BELAJAR FISIKA SISWA DI KELAS XE SMA NEGERI 3 MUARO JAMBI - Suwondo, Suwondo; Darmaji, Darmaji; Astalini, Astalini (EduFisika: Jurnal Pendidikan Fisika, 2019)
This research aims to determine the activity and learning outcomes through cooperative learning of time token type. This research was a classroom action research. The subject of this research student of XE SMAN 3 Muaro Jambi. Data collection instruments using student and teacher observation sheets during process activities as well as test learning outcomes. The results of this study showed that an increase in student activity from Cycle I was, 68.37% to 71.75% in cycle II and 74.06% in cycle III. Students ' learning results in cycles i.e., 63.03 for cycle I to 70.00 for cycle II and 76.86 for cycle III. The application of the Time Token Cooperative Learning model can increase the student's activity and learning outcomes at the temperature and heat material in the XE SMA Negeri 3 Muaro Jambi class.